1998
DOI: 10.1046/j.1469-0705.1998.11040246.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prenatal ultrasound and postmortem findings in fetuses and infants with central nervous system anomalies

Abstract: Detection of fetal developmental abnormalities by ultrasound examination of pregnant women has become a specialized field of medicine. Quality control of this field requires detailed examination of aborted fetuses. In 408 fetuses and infants with developmental anomalies, the prenatal ultrasound findings were compared with the post-mortem findings. This study focused on 140 central nervous system (CNS) anomalies. Criteria for inclusion were an ultrasound examination at the National Center for Fetal Medicine (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 28 publications
10
56
0
1
Order By: Relevance
“…23 One recent study has shown prenatal ultrasonographic diagnosis of central nervous system anomalies to have a high concordance with the autopsy diagnosis (89%). 24 This is in agreement with our study, in which postnatal and postmortem investigations confirmed the prenatal diagnosis in 13 of 15 cases (87%). Nevertheless, the prenatal sonographic distinction among such lesions may be subtle; yet differentiating these lesions is extremely important owing to the variability in prognosis, which may range from favorable to very poor.…”
Section: Discussionsupporting
confidence: 93%
“…23 One recent study has shown prenatal ultrasonographic diagnosis of central nervous system anomalies to have a high concordance with the autopsy diagnosis (89%). 24 This is in agreement with our study, in which postnatal and postmortem investigations confirmed the prenatal diagnosis in 13 of 15 cases (87%). Nevertheless, the prenatal sonographic distinction among such lesions may be subtle; yet differentiating these lesions is extremely important owing to the variability in prognosis, which may range from favorable to very poor.…”
Section: Discussionsupporting
confidence: 93%
“…it could be regarded as the incidence rate of other associated neurological conditions for the given malformation. Within the 21%, spina bifida was found to be 10%; Isaksen et al [27] reported 16% in his sample, while data by Csabay et al [22] accounted for 17%. When associated spina bifida is detected, it is worth examining which anatomical region of the vertebral column is affected.…”
Section: Color Version Available Online Color Version Available Onlinementioning
confidence: 73%
“…Corpus callosum dysgenesis should also be mentioned among the associated malformations of the central nervous system [10] . Compared to the full sample, its incidence was found to be 2.17%, while Isaksen et al [27] and Csabay et al [22] reported 3 and 2.3%, respectively.…”
Section: Color Version Available Online Color Version Available Onlinementioning
confidence: 83%
“…OF D&E SPECIMENS There are several studies 18,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] that have reviewed the correlation between prenatal ultrasound and autopsy findings, all based on examination of intact fetuses. Agreement between prenatal ultrasound findings and autopsy diagnosis when autopsy is performed on an intact fetus ranges from 45% to 91.2%.…”
Section: Value Of Careful Examinationmentioning
confidence: 99%